Coaching leaders toward favorable trajectories of burnout and engagement - Brooks, Pilar Jasmine; Ripoll, Pilar; Sánchez, Carmen; Torres, Marta (Frontiers in Psychology, 2023)
Existing literature on executive coaching has shown beneficial outcomes for leaders. Indeed, executive coaching can positively affect an individual's psychological well-being and quality of work life. However, while burnout amongst leaders is on the rise, to our knowledge no prior study has investigated the influence of executive coaching on the dimensions of burnout and engagement concurrently. Therefore, the aim of the current study is to examine if an executive coaching intervention has positive effects on managerial burnout and engagement. We implemented a tenweek coaching intervention for leaders, where questionnaire data were collected at two time points. Participants (N=92; Mage=42; 64% male) were randomly assigned to an intervention or a wait-list control group. Self-reported levels of engagement and burnout were collected at the start of the study protocol (T1) and at the end (T2). Coaching sessions for the intervention group were one hour once per week. The control group did not receive coaching. Repeated measures ANOVAs examined the extent to which the intervention influences the leader's engagement and burnout. Analyses revealed that all three dimensions of burnout significantly decreased for the intervention group over time while vigor increased. Findings did not reveal an increase in dedication and absorption. Consistent with prior literature, this study supports that executive coaching can improve a leader's well-being. Specifically, this study shows that an executive coaching intervention can decrease burnout symptoms and increase vigor in leaders. Adding a follow-up survey to the design would allow for further exploration of the intervention on engagement.